Management of gout by UK rheumatologists: a British Society for Rheumatology national audit. (13th February 2018) - Roddy, Edward; Packham, Jon; Obrenovic, Karen; Rivett, Ali; Ledingham, Joanna M
Abstract: Objectives: To assess the concordance of gout management by UK rheumatologists with evidence-based best-practice recommendations. Methods: Data were collected on patients newly referred to UK rheumatology out-patient departments over an 8-week period. Baseline data included demographics, method of diagnosis, clinical features, comorbidities, urate-lowering therapy (ULT), prophylaxis and blood tests. Twelve months later, the most recent serum uric acid level was collected. Management was compared with audit standards derived from the 2006 EULAR recommendations, 2007 British Society for Rheumatology/British Health Professionals in Rheumatology guideline and the National Institute for Health and Care Excellence febuxostat technology appraisal. Results: Data were collected for 434 patients from 91 rheumatology departments (mean age 59.8 years, 82% male). Diagnosis was crystal-proven in 13%. Of 106 taking a diuretic, this was reduced/stopped in 29%. ULT was continued/initiated in 76% of those with one or more indication for ULT. One hundred and fifty-eight patients started allopurinol: the starting dose was most commonly 100 mg daily (82%); in those with estimated glomerular filtration rate <60 ml/min the highest starting dose was 100 mg daily. Of 199 who started ULT, prophylaxis was co-prescribed for 94%. Fifty patients started a uricosuric or febuxostat: 84% had taken allopurinol previously. Of 44 commenced on febuxostat, 18% had a history of heart disease. By 12 months, serum uric acid levels ⩽360 and <300 μmol/l were achieved by 45 and 25%, respectively. Conclusion: Gout management by UK rheumatologists concords well with guidelines for most audit standards. However, fewer than half of patients achieved a target serum uric level over 12 months. Rheumatologists should help ensure that ULT is optimized to achieve target serum uric acid levels to benefit patients.